2000
DOI: 10.1023/a:1008185701106
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of the present study was to develop atransplantation technique for restoration of thyroidfunction in rats with radioiodine-inducedhypothyroidism. Each Wistar rat received the dose of75.0 muCi of 131-iodine by intraperitonealinjection. The serum thyroxine and triiodothyroninevalues in all rats fell to low levels by 2.5 weeksafter radioiodine administration. Thexenotransplantation of 3-day-old newborn pig thyroidorgan culture was performed on day 18 afterradioactive ablation by injection into the fat tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, hypothyroidism as well as radiation from 131 I also affect the expression of NOS in those patients. Several studies reported the dosage of 131 I ranging from 50 µCi to 450 µCi, and the most effective doses ranged between 75-277 µCi [17][18][19][20]. In this study, we tested 75 µCi, 150 µCi, 300 µCi, and 450 µCi dose of 131 I, and 150 µCi was selected as the optimal dose for establishing the model of hypothyroidism in rats.…”
Section: C B Amentioning
confidence: 99%
See 1 more Smart Citation
“…However, hypothyroidism as well as radiation from 131 I also affect the expression of NOS in those patients. Several studies reported the dosage of 131 I ranging from 50 µCi to 450 µCi, and the most effective doses ranged between 75-277 µCi [17][18][19][20]. In this study, we tested 75 µCi, 150 µCi, 300 µCi, and 450 µCi dose of 131 I, and 150 µCi was selected as the optimal dose for establishing the model of hypothyroidism in rats.…”
Section: C B Amentioning
confidence: 99%
“…injected with 131 I to establish a model of hypothyroidism. According to the literature, the dosage of 131 I ranged from 50-450 µCi and the longest exposure lasted 5 months [17][18][19][20]. In our experiments, the rats in different groups were i.p.…”
Section: Introductionmentioning
confidence: 99%